The representation of the Spanish Crown in the public sphere through institutional acts (Communication & Society, 2021)
The main objective of this work is to analyse how the representation in the public sphere of the Crown and the Head of the Spanish State is managed towards public opinion through public, official, and unofficial institutional acts, as reported by the House of H. M. the King. To answer the research questions contained in this objective, a quantitative methodological design based on content analysis is carried out (Krippendorff, 2002). This is applied to a corpus of the 996 public, official, and unofficial acts, contained in the web institution of the House of H. M. the King, between 2015 and 2019, for its subsequent computer processing with SPSS statistical software. Through the concept of intramethod triangulation, a qualitative analysis is applied in an auxiliary way to answer RQ3. The results show not only that the presence of the Royal Family, in the acts observed, contributes towards the public staging of its constitutional functions, but also that there is a map of specific audiences on which the Royal House projects pertinent legitimising messages (regarding the Crown and the Head of State) based on perceived social demands. This confirms the existence of a dialogical communication system, supported by a strategic conception of Crown-society relations, which is resolved mainly through ceremonial acts.